Profiling the Aerobic Window of Horses in Response to Training by Means of a Modified Lactate Minimum Speed Test: Flatten the Curve - De Maré, Lorie; Boshuizen, Berit; Vidal Moreno de Vega, Carmen; de Meeûs, Constance; Plancke, Lukas; Gansemans, Yannick; Van Nieuwerburgh, Filip; Deforce, Dieter; de Oliveira, Jean Eduardo; Hosotani, Guilherme; Oosterlinck, Maarten; Delesalle, Catherine (Frontiers in Physiology, 2022)
There is great need for objective external training load prescription and performance capacity evaluation in equestrian disciplines. Therefore, reliable Standardized Exercise Tests (SETs) are needed. Classic SETs require maximum intensities with associated risks and deduce training loads from pre-described cut-off values. The Lactate Minimum Speed (LMS) test could be a valuable alternative. Our aim was to compare new performance parameters of a modified LMS-test with those of an incremental SET; to assess the effect of training on LMS-test parameters and curve-shape; to identify the optimal mathematical approach for LMS-curve parameters. Six untrained Standardbred mares (3-4 years) performed a SET and LMS-test at the start and end of 8 weeks harness training. SET-protocol contains 5 increments (4km/h; 3 minutes/step). LMS-test started with 3 minutes trot at 36-40km/h (until blood lactate (BL) >5mmol/L) followed by 8 incremental steps (2km/h; 3minutes/step). Maximum Lactate Steady State estimation (MLSS) entailed >10 km run at respectively LMS and 110%LMS. GPS, heartrate (Polar®) and BL were monitored and plotted. Curve-parameters (R core team, 3.6.0) were: (SET) VLa1.5/2/4 and (LMS-test) AUC>/0.80), Bland-Altman method and OLP regression analyses were determined for test-correlation and concordance. Training induced a significant increase in Vla1.5/2/4. The width of the AW increased significantly while the AUCLMS and LMS decreased post-training (flattening U-curve). The LMS BL steady-state is reached earlier and maintained longer after training. BLmax was significantly lower for LMS vs SET. The 40°-angular method is the optimal approach. The correlation between LMS and VMLSS was significantly better compared to SET. The VLa4 is unreliable for equine aerobic capacity assessment. The LMS-test allows more reliable individual performance capacity assessment at lower speed and BL compared to SETs. The LMS-test protocol can be further adapted, especially post-training, however, inducing modest hyperlactatemia prior to the incremental LMS-stages and omitting inclusion of a per-test recovery contributes to its robustness. This LMS-test is a promising tool for development of tailored training programs based on the AW respecting animal welfare.